Nilai-Nilai Pendidikan Sosial dalam Al-Qur’an Surat Ali Imran Ayat 134 (Analisis Tafsir Al-Qur’an Al-Azhim Karya Ibnu Katsir) - Muttaqin, Abdul Aziz Zaenal; Ainusyamsi, Fadlil Yani; Iswanto, Pepe (Bestari, 2020)
This study aims to determine: (1) the content of the al-Qur'an surah Ali Imran verse 134; (2) the values ​​of social education contained in al-Qur'an surah Ali Imran verse 134 according to Ibn Katsir's Tafsir al-Qur'an al-Azhim; (3) the relevance of the value of education in al-Qur'an surah Ali Imran verse 134 with today's education. This study uses the Maudhu'iy (thematic) method, namely the method of interpreting the verses of the Qur'an according to a particular theme or topic. Meanwhile, the data collection technique used in this research is literature study or documentation. The data analysis technique used in this study is the Moleong data analysis technique, which includes the stages of data reduction, data display, drawing conclusions and verification. After analyzing the data, the authors obtained the following conclusions: first, the contents of the al-Qur'an Surah Ali Imran verse 134 describes the characteristics of a pious person. Secondly, Ibn Kathir also said that the al-Qur'an surah Ali Imran verse 134 describes the characteristics of a pious person, including 1) Berinfaq in a field or narrow, happy or difficult. 2) Hold back anger when able to vent it. 3) Forgive those who wrong us even without being asked. 4) Do well. Apart from being the characteristics of a pious person, these four characteristics are also included in the values ​​of social education, where these traits cannot be realized without social interaction with other people. third, the values ​​of social education contained in al-Qur'an surah Ali Imran verse 134 when connected with contemporary education are very relevant, given the importance of these values ​​to be possessed by educators and students and society in general.